2009
DOI: 10.1371/journal.pone.0004599
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Evaluation of a Multivariate Index Assay for Ovarian Cancer

Abstract: BackgroundMost women with a clinical presentation consistent with ovarian cancer have benign conditions. Therefore methods to distinguish women with ovarian cancer from those with benign conditions would be beneficial. We describe the development and preliminary evaluation of a serum-based multivariate assay for ovarian cancer. This hypothesis-driven study examined whether an informative pattern could be detected in stage I disease that persists through later stages.Methodology/Principal FindingsSera, collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…These bootstrap estimates allowed us to assess the potential value of many models using only the training data. In this way we were able to maintain the independence of the hold-out testing set of samples [10]. Figure 2 shows the modeling process to find the optimum biomarkers and classify.…”
Section: Figure 1 Auc Convergence Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…These bootstrap estimates allowed us to assess the potential value of many models using only the training data. In this way we were able to maintain the independence of the hold-out testing set of samples [10]. Figure 2 shows the modeling process to find the optimum biomarkers and classify.…”
Section: Figure 1 Auc Convergence Graphmentioning
confidence: 99%
“…Therefore methods to distinguish women with ovarian cancer from those with benign conditions would be beneficial [10].…”
Section: Introductionmentioning
confidence: 99%
“…CA125 is only promising tumor marker currently, but it is low specificity. In combination with CA125, other serum tumor markers have been evaluated to improve the accuracy with some limitations (Visintin, Feng et al 2008;Amonkar, Bertenshaw et al 2009;Nosov, Su et al 2009). The study in 2008 evaluated various combinations of 9 markers including CA125, HE4, SMRP, CA72-4, Osteopontin, ERBB2, Inhibin, Activin, and EGFR.…”
Section: Single/multiple Tumor Markersmentioning
confidence: 99%
“…Thus, CA125 has low sensitivity in early-stage disease and additional ultrasonography or combinations of other markers are required [9][10][11]. In recent years, a number of studies have confirmed that combinations of CA125 and other biomarkers provided improved diagnostic performance for early-stage ovarian cancer [5][6][7][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the women with clinical features that correspond to ovarian cancer have benign conditions, and thus it is important to detect early ovarian cancer in women with benign conditions [11].…”
Section: Introductionmentioning
confidence: 99%